2008
DOI: 10.1111/j.1863-2378.2007.01096.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Diagnostic Accuracy of theinvA‐gene‐based PCR Technique and a Bacteriological Culture for the Detection ofSalmonellaspp. in Caecal Content from Slaughtered Pigs using Bayesian Analysis

Abstract: The goal of this study was to estimate the accuracy of the invA-gene-based polymerase chain reaction (PCR) and a culture technique based on pre-enrichment with buffered peptone water, three selective enrichment media (selenite, tetrathionate and Rappaport-Vassiliadis broths) and four selective, solid media (Xylose-Lysine-Tergitol-4, Salmonella/Shigella, Hekton-Enteric and MacConkey), for the detection of Salmonella organisms from caecal samples from slaughter pigs. For this purpose a latent-class (Bayesian) ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 30 publications
(61 reference statements)
1
19
0
Order By: Relevance
“…Overall, these results confirmed that the Se ISO was somewhat below 87.6%, which is rather high for a culture protocol and higher than most of the results reported from other studies using different culture protocols and matrices (9,10,14,(24)(25)(26). Both the large amount of sample (25 g) and the repeated enrichment and subculturing in different media used by ISO would have had an effect on the recovery of Salmonella organisms (7,10,11) and would explain this high overall Se ISO .…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…Overall, these results confirmed that the Se ISO was somewhat below 87.6%, which is rather high for a culture protocol and higher than most of the results reported from other studies using different culture protocols and matrices (9,10,14,(24)(25)(26). Both the large amount of sample (25 g) and the repeated enrichment and subculturing in different media used by ISO would have had an effect on the recovery of Salmonella organisms (7,10,11) and would explain this high overall Se ISO .…”
Section: Discussionsupporting
confidence: 58%
“…(32). Regarding the Sp PCR , it has been suggested that it may be affected by the proportion of potential cross-reacting bacteria in the guts of the animals sampled in each population (14). Hence, it was decided to check the assumption of constant test accuracy across populations by running separate Bayesian analyses of the two populations (39).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bacteriology, the method of reference, is expensive, tedious, time-consuming and less sensitivity, particularly when performed on feces (Hurd et al, 2004;Mainar-Jaime et al, 2008a), making this approach unfeasible for large-scale control programs. Serology is thus foreseen as one of the best alternatives.…”
Section: Introductionmentioning
confidence: 99%